2017
DOI: 10.11607/prd.2747
|View full text |Cite
|
Sign up to set email alerts
|

Peri-implant Soft Tissue Stability After Single Implant Restorations Using Either Guided Bone Regeneration or a Connective Tissue Graft: A Randomized Clinical Trial

Abstract: The purpose of the present study was to compare two different surgical procedures, connective tissue graft and guided bone regeneration, when applied in conjunction with implant placement. Probing pocket depth and the recession depth were recorded at the implant site after crown placement (T₁) and at the 1-year follow-up (T₂), while the keratinized tissue height and the buccal mucosa thickness were recorded at three different time points: at the time of implant surgery (T₀), after crown placement, and at the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…The risk of bias in eight included RCTs were assessed and summarized (Table ), two studies (Bianchi & Sanfilippo, ; Sanz et al., ) (25%) of unclear risk of bias for allocation concealment, one study (Bianchi & Sanfilippo, ) (12.5%) of high risk, and two studies (Sanz et al., ; Zuiderveld et al., ) (25%) of unclear risk of bias for participants and personnel, and one study (D'Elia et al., ) (12.5%) with selective reporting due to no baseline data. Also, most of the included articles (7 of 14, 87.5%) revealed an unclear risk of bias for blinding of the outcome assessment (Bianchi & Sanfilippo, ; Cairo et al., ; D'Elia et al., ; Lorenzo et al., ; Sanz et al., ; Zeltner et al., ; Zuiderveld et al., ). Only one controlled clinical trial had seven stars and showed the “medium–high” level of evidence (Wiesner et al., ) (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The risk of bias in eight included RCTs were assessed and summarized (Table ), two studies (Bianchi & Sanfilippo, ; Sanz et al., ) (25%) of unclear risk of bias for allocation concealment, one study (Bianchi & Sanfilippo, ) (12.5%) of high risk, and two studies (Sanz et al., ; Zuiderveld et al., ) (25%) of unclear risk of bias for participants and personnel, and one study (D'Elia et al., ) (12.5%) with selective reporting due to no baseline data. Also, most of the included articles (7 of 14, 87.5%) revealed an unclear risk of bias for blinding of the outcome assessment (Bianchi & Sanfilippo, ; Cairo et al., ; D'Elia et al., ; Lorenzo et al., ; Sanz et al., ; Zeltner et al., ; Zuiderveld et al., ). Only one controlled clinical trial had seven stars and showed the “medium–high” level of evidence (Wiesner et al., ) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Different methods/tools were used for soft tissue assessment, which include but are not limited to sounding with stopper, ultrasonic device, cast‐superimposed technique, and three dimension image based on intraoral photos (Zeltner et al., ). To minimize the possible bias, the meta‐analysis of STT merely included the data from sounding (D'Elia et al., ; Wiesner et al., ; Zucchelli et al., ) and ultrasonic measurement (De Bruyckere et al., ). To be more specific, the details in STT change for ultrasonic device could be up to 0.01 mm, which is more accurate than the conventional tools (endodontic ruler, caliper, or periodontal probe).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RCTs demonstrated significantly less midfacial recession following the application of a connective tissue graft in the buccal mucosa following IIP (Frizzera et al., ; Yoshino, Kan, Rungcharassaeng, Roe, & Lozada, ; Zuiderveld, Meijer, den Hartog, Vissink, & Raghoebar, ). Connective tissue grafts also appear beneficial to restore buccal convexity following DIP (D'Elia et al., ; De Bruyckere, Eghbali, Younes, De Bruyn, & Cosyn, ; De Bruyckere et al., ; Eghbali, De Bruyn, Cosyn, Kerckaert, & Hoof, ; Eghbali et al., ; Hanser & Khoury, ; Stefanini et al., ). Clearly, state‐of‐the‐art implant therapy often requires soft tissue grafting following IIP as well as following DIP.…”
Section: Discussionmentioning
confidence: 99%